ANALISIS STRUKTUR MODAL DALAM MENINGKATKAN PROFITABILITAS PT. MATAHARI DEPARTMENT STORE TBK - Shella Jelita Anshari; Rahmat Daim Harahap; Muhammad Ridwan (FEB Universitas Syiah Kuala, 2023)
This study aims to analyze how the capital structure in increasing profitability at PT. Matahari Department Store Tbk and to find out what causes tend to decrease profitability at PT. Matahari Department Store Tbk. The approach used in this study is a descriptive qualitative approach. The data analysis technique used is descriptive analysis. Based on the results of research conducted capital structure is still not able to increase profitability at PT. Matahari Department Store Tbk which can be seen from the fluctuating (unstable) capital structure causes profitability to tend to decrease. This was due to falling sales due to the pandemic and also increasing corporate debt. Decrease in profitability at PT. Matahari Department Store is caused by several factors including the company has not been effective in managing its working capital to generate income which can be seen from the turnover of working capital and total assets which for the past six years have not been good enough to contribute to sales and the worsening financial condition of the company which in In 2020 the company experienced a loss of Rp. 873 billion and this is one of the causes of decreased profitability at PT. Matahari Department Store Tbk.